Relacionamento e fidelização de clientes de uma corretora de seguros: estudo de caso - Pimentel, Elisson Pereira (2021)
The present work had as objective to analyze the customers of the company GM Seguros, trying to identify if they are satisfied with the services provided by the company. With this, we seek to measure how the level of customer satisfaction is, where the more satisfied, the more loyal these customers tend to be. For this, at first, a qualitative research was applied, aiming to identify the customer's needs in relation to this market; soon after, a quantitative survey was applied, where a number of 63 respondents were obtained, where the level of trust, commitment, satisfaction, repurchase and recommendation with the company's customers were measured. With this, it can be seen that the company is on the right path, considering that the results were that the company has a good rate of customer satisfaction, making them faithful at the time of the repurchase process. And it was also identified that the index that most needs attention was the recommendation, which the company should focus on to generate “word of mouth marketing”.